-7(-5+a)=-3(1-4a)

Simple and best practice solution for -7(-5+a)=-3(1-4a) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7(-5+a)=-3(1-4a) equation:



-7(-5+a)=-3(1-4a)
We move all terms to the left:
-7(-5+a)-(-3(1-4a))=0
We add all the numbers together, and all the variables
-7(a-5)-(-3(-4a+1))=0
We multiply parentheses
-7a-(-3(-4a+1))+35=0
We calculate terms in parentheses: -(-3(-4a+1)), so:
-3(-4a+1)
We multiply parentheses
12a-3
Back to the equation:
-(12a-3)
We get rid of parentheses
-7a-12a+3+35=0
We add all the numbers together, and all the variables
-19a+38=0
We move all terms containing a to the left, all other terms to the right
-19a=-38
a=-38/-19
a=+2

See similar equations:

| 5x+10/5=1 | | 3x-4x+5=5x+17 | | 5x-(8x+6)=5x-22 | | 5x-4=3×+10 | | {x}-3=5 | | 3k-9=18 | | 3x-53=4x+21-x | | 7x/6=-28 | | 5(x-1)=2(×-4)-6 | | a/3-7=2 | | 180=7x-3x(-6x+15) | | 16x-(6x-7)=77 | | 3x+13-4=4 | | 5x+6x-19=76-8x | | -172=4x-6(3x+17) | | 8+z=-18 | | -(9-6x)=4(7x-3)-22x+3 | | 6x-2-3x-5)=154 | | 6n+3n=21 | | 6x-2-3x-5)=254 | | 18+6x+13=1 | | 2(2/3+1.5x)=3/4+10× | | 5/2–3x–5+4x=7/4 | | 4a+8a=16-4a | | 1/5x+1/3=4 | | –3x–5+4x=– | | -80=-4/3x+20 | | (6x+48)+(3x+60)=180 | | –4y+8=4(2y –2) –2(–16+8y) | | 5x+4(x-1)=4-x*3 | | 9(u–2)+1.5u=8.25 | | (2x-5)^2=54 |

Equations solver categories